LAMAS (Light, Activity, Meals, & Sleep) timings & burnout, anxiety, and depression in teachers: Protocol for a cross-sectional study - Marius König; Jonas P. Wallraff; Florian Glenewinkel; Ursula Wild; Thomas C. Erren; Philip Lewis (PLoS ONE, 2026)
Background Teachers play a key role in society and make up ~1.5–2.5% of the working population. Yet, there is a teacher shortage in many countries and preventive occupational medicine strategies are called for. The primary objective of this project is to explore single and joint associations of the diurnal distributions of light, activity, meal, and sleep timing and work-related exposures with severity scores of burnout, anxiety, and depression in a cross-sectional study of secondary school teachers in Germany. Methods and analysis The study will involve a one-time collection of questionnaire-based data on sleep, burnout, anxiety, and depression, sensor-based data on light and activity over one week, and diary-based data on work, sleep, and meals over one week. time. The protocol has been registered on the Open Science Framework ( https://doi.org/10.17605/OSF.IO/U4R5M ). Discussion From a preventive occupational medicine perspective, identifying where and how light, activity, meal, and sleep timing may be targeted to mitigate burnout, anxiety, and depression could inform measures to be tested not only at the individual (micro) level, but also at systems (meso-institutions; macro-policy and society) levels.